(untitled) (Research, Society and Development, 2022)
In March 2020, the World Health Organization declared a COVID-19 pandemic, with approximately 192 million infected by July 2021. Pregnant women are a population of high vulnerability to the worsening of the disease, as 27% of them had adverse effects, such as interruption of pregnancy. This study aims to analyze the factors that promote susceptibility to infection and worsening by SARS-CoV-2 in pregnant women. This is a narrative review of the literature carried out from April to November 2021. It was found that, in pregnancy, the circulatory system presents endothelial dysfunction and activation of the coagulation system, a finding associated with the prothrombotic state generated by SARS-CoV-2, favoring the occurrence of pathologies such as stroke. The increase in progesterone during pregnancy stimulates changes in the respiratory system that decrease functional residual capacity and generate hypoxia intolerance, allowing greater susceptibility to virus infection. This hormonal increase alters the Th1 and Th2 immune profile, an imbalance also found in COVID-19, contributing to vulnerability. As for perinatal repercussions, the virus spreads across the placenta, triggering a cross-response with the maternal immune system, placental hypoperfusion and other complications. It is concluded that the sum of the factors found in the pregnant woman infected by the virus makes her more vulnerable to the severe form of the disease and to fetal complications.